New essays on ancient Pyrrhonism - Machuca, Diego E. (Philosophia Antiqua, 2011)
Scholarship on ancient Pyrrhonism has made tremendous advances over the past three decades, thanks especially to the careful reexamination of Sextus Empiricus' extant corpus. Building on this momentum, the authors of the eight essays collected here examine some of the most vexed and intriguing exegetical and philosophical questions posed by Sextus' presentation of this form of skepticism. The essays explore in a new light the skeptical interpretation of Plato, the differences between Pyrrhonism and Cyrenaicism, the Pyrrhonist's stance on ordinary life, religion, language, and ethics, Sextus' discussion of our access to our own mental states, and the relationship between Pyrrhonism and epistemic internalism and externalism. These new essays represent a substantial contribution to the advancement of scholarship on Pyrrhonian skepticism.